The Structure of the Salmonella typhimurium Type III Secretion System Needle Shows Divergence from the Flagellar System - Galkin, Vitold E. (2010)
The Type III Secretion System (T3SS) is essential for the infectivity of many pathogenic Gram-negative bacteria. The T3SS contains proteins that form a channel in the inner and outer bacterial membranes, as well as an extracellular needle that is used for transporting and injecting effector proteins into a host cell. The homology between the T3SS and the bacterial flagellar system has been firmly established, based upon both sequence similarities between respective proteins in the two systems and the structural homology of the higher-order assemblies. It has previously been shown that the Shigella flexneri needle has a helical symmetry of ~ 5.6 subunits per turn, which is quite similar to that of the most intensively studied flagellar filament, from Salmonella typhimurium, which has ~ 5.5 subunits per turn. We now show that the S. typhimurium needle, expected by homology arguments to be more similar to the S. typhimurium flagellar filament than is the needle from Shigella, actually has ~ 6.3 subunits per turn. It is not currently understood how host cell contact, made at the tip of the needle, is communicated to the secretory system at the base. In contrast to the S. typhimurium flagellar filament, which shows a nearly crystalline order, the S. typhimurium needle has a highly variable symmetry, which could be used to transmit information about host cell contact.